Key Factors Influencing Consumer Purchasing Decisions in Digital Era - Tegar, Tegar; Sari, Citra Mulya (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2025)
This study examines the combined impact of digital marketing, strategic location, brand equity, and price perception on consumer purchasing decisions in the furniture industry, specifically at Mebel Mandiri. By integrating digital transformation and behavioral economics, it provides insights into consumer decision-making dynamics. Using a quantitative associative approach, data was collected through online questionnaires from 33 respondents and analyzed with SPSS 20, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, and F and T-tests. The findings reveal that digital marketing and price perception significantly influence purchasing decisions, while location and brand equity do not. Together, these variables account for 72.2% of purchasing decisions, with 27.8% influenced by other factors. This study emphasizes that digital marketing strategies and competitive pricing are critical for increasing consumer purchases. Businesses should enhance interactive and credible digital content while ensuring prices reflect product benefits. Additionally, this research highlights the importance of digital marketing and price perception in boosting SMEs' competitiveness, promoting digital transformation, and fostering fair pricing to build consumer trust. Strengthening these strategies expands market reach, enhances business resilience, and contributes to economic sustainability. The study suggests that companies invest in targeted digital campaigns and data-driven pricing strategies to attract and retain customers. By implementing these approaches, businesses can not only increase sales but also drive local economic growth, create job opportunities, and support long-term business sustainability. Ultimately, digital marketing and pricing strategies play a vital role in shaping the future of SMEs in the digital era.